In The Era of Precision Medicine- Where Does the Diagnosis “Hypertensive Kidney Disease” Fit? - Lohani, Sadichhya; Atta, Mohamed G. (Archives of Clinical and Medical Case Reports, 2020)
Hypertension has been labeled as a cause of non-diabetic chronic kidney disease for decades. In today’s era of precision medicine, labeling benign hypertension as the initial etiology for chronic kidney disease might not be accurate. We discuss an example of a 55-year-old African American patient with pathologic findings of nephrosclerosis without history of hypertension. The pathologic findings of nephrosclerosis can be as a result of obesity, aging, genetic susceptibility and variety of other previously undiagnosed primary renal disease, and hence shouldn’t automatically mark the diagnosis of hypertensive nephrosclerosis. Multiple studies to date have failed to prove or refute causality between benign hypertension and non-diabetic chronic kidney disease. Genome sequencing of non-diabetic kidney diseases have identified mutations in Apolipoprotein L1 gene, MYH9 gene and uromodulin gene as a risk factors for chronic kidney disease. There is no question that uncontrolled hypertension leads to progression of kidney disease, and hence blood pressure should be controlled adequately. The relationship between hypertension and kidney dysfunction should be viewed as an association and broad differential diagnoses should be pursued.